Internationalization strategies of a multilatina in the service sector: Avianca-Taca holdings S.A. case study (2019)
This paper explores how existing internationalization theories can be applied to a Multilatina in the service sector, using the case of Avianca-Taca Holdings S.A. as an example. This paper introduces the company by analyzing the context in which it grew, starting with the service sector in Colombia, which is its country of origin. This paper also analyzes the international and domestic air transportation industry alongside the history of Avianca-Taca Holdings S.A. It describes in detail the internationalization program undertaken by the company and analyzes it based on three existing theories that may explain why such choices were made instead of others available. This paper explores different applications of these traditional theories. By this token, it concludes that, rather than using a brand new theory and aspiring to cover a large array of services, it is wiser to make decisions with a more comprehensive scope and use existing theories to adapt an efficient internationalization strategy to a particular context, region or country.